Cornwallis in Bengal - Aspinall, A. (Arthur), 1901- (New Delhi : Uppal Pub. House, 1987)
On the administrative and judicial reforms in India; includes the expansion of the East India Company, 1786-1793, and the foundation of Penang.
Reprint. Originally published: Manchester : Manchester University Press, 1931.
Includes index.
Appendix (p. 177-205): 1. The Company's trade in the time of Cornwallis -- 2. The beginnings of Penang, 1786-93.
Bibliography: p. xiii-xv.
Keywords: Cornwallis, Charles Cornwallis -- Marquis, -- 1738-1805.; East India Company -- History; Bengal (India) -- Politics and government; India -- Politics and government -- 19th century